2013
DOI: 10.1111/j.1365-4632.2012.05708.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin tumors and skin infections in kidney transplant recipients vs. patients with pemphigus vulgaris

Abstract: Pemphigus vulgaris in prolonged immunosuppression is immunoprotective against skin infections and skin tumors while kidney transplant recipients are not protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Sharquie et al . concluded that PV in prolonged immunosuppression is immunoprotective against skin infections and skin tumors compared with kidney transplant recipients . Therefore, from these above opinions, we think it may be merely a secondary infection due to his abuse of oral antimicrobials, lack of shampoo, and accumulation of lots of fatty scales.…”
Section: Localized Pemphigus Vulgaris On the Scalpmentioning
confidence: 91%
“…Sharquie et al . concluded that PV in prolonged immunosuppression is immunoprotective against skin infections and skin tumors compared with kidney transplant recipients . Therefore, from these above opinions, we think it may be merely a secondary infection due to his abuse of oral antimicrobials, lack of shampoo, and accumulation of lots of fatty scales.…”
Section: Localized Pemphigus Vulgaris On the Scalpmentioning
confidence: 91%
“…In all autoimmune diseases, there should be destruction of some specific tissue induced by autoimmune reaction whether humeral or cell mediated that result in specific diseases like pemphigus, vitiligo and alopecia areata. But on the other hand, these enhanced exaggerated immune reactions could be protective for other specific diseases in the same patients and this idea had been recently supported by Sharquie et al where they found autoimmune diseases like pemphigus and lupus erythematosus are protective against any skin tumors like BCC, SCC and Kaposi's sarcoma and infections like fungal infection warts [6].…”
Section: Discussionmentioning
confidence: 92%
“…From daily clinical practice, we have noticed that many patients with autoimmune disease had lower frequency of infections and skin tumors. Sharquie et al had confirmed this hypothesis especially in relation to pemphigus vulgaris and systemic lupus erythematosus and the results were very encouraging [6]. These results encouraged to conduct a study in patients with vitiligo where it was found that patients with vitiligo had lower frequency of malignancy and this was attributed to high P53 in lesional and perilesional skin compared to normal skin [7].…”
Section: Introductionmentioning
confidence: 90%
“…So, the present work had confirmed the high positivity of P53 marker in vitiligo skin and its role in protection against skin cancers. A most recent study showed that autoimmune diseases like pemphigus are protective against skin malignancies in kidney transplant recipients [7] and as vitiligo is autoimmune disorder, it might also have such protection.…”
Section: Discussionmentioning
confidence: 99%
“…A most recent study showed that autoimmune diseases like pemphigus vulgaris and systemic lupus erythematous showed absence of skin malignancies among those patients although they had received a prolonged course of immunosuppressive therapy as a result of active immune surveillance in those patients [7]. Also, on a recent study, it was reported that the tumor suppressive marker p53 is increased among patients with vitiligo [8].…”
Section: Introductionmentioning
confidence: 99%